Genetic diversity of zoonotic malaria parasites from mosquito vector and vertebrate hosts - Wong, Meng Li; Ahmed, Md Atique; Wan Sulaiman, Wan Yusoff; Manin, Benny O.; Leong, Cherng Shii; Quan, Fu-Shi; Chua, Tock H.; Drakeley, Chris; Snounou, Georges; Vythilingam, Indra (Elsevier, 2019)
We explored and constructed haplotype network for simian malaria species: Plasmodium knowlesi, P. cynomolgi and P. inui aiming to understand the transmission dynamics between mosquitoes, humans and macaques. Mosquitoes were collected from villages in an area where zoonotic malaria is prevalent. PCR analysis confirmed Anopheles balabacensis as the main vector for macaque parasites, moreover nearly 60% of the mosquitoes harboured more than one Plasmodium species. Fragments of the A-type small subunit ribosomal RNA (SS rRNA) amplified from salivary gland sporozoites, and equivalent sequences obtained from GenBank were used to construct haplotype networks. The patterns were consistent with the presence of geographically distinct populations for P. inui and P. cynomolgi, and with three discrete P. knowlesi populations. This study provides a preliminary snapshot of the structure of these populations, that was insufficient to answer our aim. Thus, collection of parasites from their various hosts and over time, associated with a systematic analysis of a set of genetical loci is strongly advocated in order to obtain a clear picture of the parasite population and the flow between different hosts. This is important to devise measures that will minimise the risk of transmission to humans, because zoonotic malaria impedes malaria elimination. © 2019